Making Space for Feminist Social Critique in Contemporary Kerala - J DEVIKA , MINI SUKUMAR (Economic and Political Weekly, 2006)
Women’s literary writing in Kerala has gained a fairly wide market. Even as younger women authors have succeeded in breaking earlier stereotypes and frameworks of depiction, the category of ‘pennezhuthu’ has come to be questioned as a defining term that limits, instead of enabling. Incisive feminist critiques of contemporary patriarchy now draw upon a variety of disciplines, with the result that long held notions defining Malayalee womanhood are being questioned with increasing regularity. Concomitantly, stereotyped frameworks and the pulls of the market continue to exercise a powerful influence. It makes it all the more necessary to foster independent initiatives in feminist knowledge generation in Kerala. “Women’s Imprint”, a women’s publishing venture in Malayalam is involved in such efforts to help create new networks of resistance and towards ensuring that gender remains a contested category in public debate.